2016
DOI: 10.1002/cssc.201601269
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reaction Mechanism of Glycerol Hydrogenolysis over a CuCr2O4Catalyst

Abstract: The reaction mechanism of glycerol hydrogenolysis to 1,2-propanediol over a spinel CuCr O catalyst was investigated by using DFT calculations. Theoretical models were developed from the results of experimental characterization. Adsorption configurations and energetics of the reactant, intermediates, final product, and transition states were calculated on Cu(1 1 1) and CuCr O (1 0 0). Based on our DFT results, we found that the formation of acetol is preferred to that of 3-hydroxypropionaldehyde thermodynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Sato et al and Huang et al , proposed Cu nanoparticles catalyzed dehydration-hydrogenation mechanism by observing acetol intermediate produced by dehydration of glycerol. Yi et al also observed acetol (14.3% in carbon selectivity) as well as 1,2-propanediol (52.6%), ethylene glycol (3.6%), and 1-propanol (15.3%) in glycerol hydrogenolysis over bulk Cu catalyst (7.5 M C 3 H 8 O 3 in H 2 O, 4.0 MPa H 2 , 493 K, 12 h) . Based on the ex situ XPS analysis of bulk Cu and Cu/SiO 2 catalysts showing both Cu 0 and Cu 2+ , , partially oxidized Cu species (Cu x O) may be present on the catalyst surface during the reaction, which can provide a Lewis acid site.…”
Section: Hydrogenolysis Of Biomass-derived Oxygenatesmentioning
confidence: 96%
See 1 more Smart Citation
“…Sato et al and Huang et al , proposed Cu nanoparticles catalyzed dehydration-hydrogenation mechanism by observing acetol intermediate produced by dehydration of glycerol. Yi et al also observed acetol (14.3% in carbon selectivity) as well as 1,2-propanediol (52.6%), ethylene glycol (3.6%), and 1-propanol (15.3%) in glycerol hydrogenolysis over bulk Cu catalyst (7.5 M C 3 H 8 O 3 in H 2 O, 4.0 MPa H 2 , 493 K, 12 h) . Based on the ex situ XPS analysis of bulk Cu and Cu/SiO 2 catalysts showing both Cu 0 and Cu 2+ , , partially oxidized Cu species (Cu x O) may be present on the catalyst surface during the reaction, which can provide a Lewis acid site.…”
Section: Hydrogenolysis Of Biomass-derived Oxygenatesmentioning
confidence: 96%
“…6%), and 1-propanol (15.3%) in glycerol hydrogenolysis over bulk Cu catalyst (7.5 M C 3 H 8 O 3 in H 2 O, 4.0 MPa H 2 , 493 K, 12 h) 124. Based on the ex situ XPS analysis of bulk Cu and Cu/SiO 2 catalysts showing both Cu 0 and Cu 2+ ,122,125 partially oxidized Cu species (Cu x O) may be present on the catalyst surface during the reaction, which can provide a Lewis acid site.…”
mentioning
confidence: 99%
“…In 2017 the adsorption, configurations and energetics of the reactants, intermediates and final products of the GL hydrogenolysis on metallic Cu were studied and compared with spinel CuCr 2 O 4 , by DFT experiments. [55] They observed that the formation of HAc (by cleavage of the terminal hydroxyl group), as intermediate, is thermodynamically and kinetically favored to that of 3-HPA (by cleavage of the central hydroxyl group), for both catalysts, leading to 1,2-PD as main reaction product (Scheme 6). The Cu species are the real active catalyst for the CÀ O cleavage, whereas the Cr atom gives to GL a stable adsorption site to facilitate CÀ O cleavage by the copper in the dehydration step, that is the rate-limiting step.…”
Section: Chromiummentioning
confidence: 99%
“…The authors declared 32 % of GL conversion and a 1,2-PD yield of 24 %. [55] Recently, chromium silicates with MFI structure were tested as heterogeneous catalysts for gaseous GL conversion into acetaldehyde and Acr as main products. The reaction was performed at 773 K under atmospheric pressure in a continuous-flow glass fixed-bed reactor, leading to high GL conversion (97 %) to acetaldehyde and Acr in a 30 % and 10 % yield, respectively.…”
Section: Chromiummentioning
confidence: 99%
“…Revelaron que la formación de AcOH está favorecida tanto termodinámicamente como cinéticamente en la superficie del Cu y de la espinela de CuCr2O4. La baja energía de activación encontrada para la formación de 1,2-PG sobre la superficie de la espinela CuCr2O4 se debe exclusivamente a su estructura, otorgando los sitios adecuados para la adsorción del glicerol, su deshidratación y la posterior hidrogenación del AcOH [57].…”
Section: Cobreunclassified